Holocene evolution of a proglacial lake in southern Kamchatka, Russian Far East. (27th August 2021) - Nazarova, Larisa; Sachse, Dirk; Fuchs, Harald G. E.; Dirksen, Veronika; Dirksen, Oleg; Syrykh, Liudmila; Razjigaeva, Nadezhda G.; Rach, Oliver; Diekmann, Bernhard
Abstract : The Kamchatka Peninsula (Russian Far East) remains among the least studied regions of eastern Asia. Recent studies revealed a high degree of palaeoenvironmental variability between different parts of the peninsula. We investigated semi‐aquatic (chironomids) and terrestrial (leaf wax biomarkers) proxies from a sediment core collected from Lake Sokoch (southern Kamchatka) to provide reconstruction of the mean July air temperature and variations in limnic conditions. The lake formed after 10.0 cal. ka BP as a result of postglacial warming and was fed by glacial meltwaters from neighbouring glaciers. Our data show a later beginning of the Holocene thermal maximum (HTM) relative to more northern sites in Kamchatka, Siberia and Chukotka and support climate model experiments that suggest that the HTM was delayed in southern and central Kamchatka by about 2000 years compared with Alaska and NE Siberia. Warm conditions prevailed between 10.0 and 6.4 cal. ka BP with a short spell of cool and dry climate around 8.2 cal. ka BP that might be related to the 8.2 ka cooling event. The HTM took place between 6.5 and 3.4 cal. ka BP with the warmest phase from 6.0 to 5.0 cal. ka BP. An onset of Neoglacial cooling at 3.4 cal. ka BP is consistent with the strengthening of both the Siberian High and the Aleutian Low. Warming between 1.2 and 0.9 cal. ka BP can be attributed to the Mediaeval Climate Anomaly. The LIA cooling is related to another strengthening of the Siberian High and the Aleutian Low. The modern warming, though weakly traced in our record, is consistent with the recent meteorological observations. The presented palaeoenvironment record confirms the earlier findings of spatial differences within Kamchatka in timing and magnitude of the major Holocene climate fluctuations and contributes towards understanding the expression of Holocene climate change in Kamchatka.